2021
DOI: 10.1182/blood-2021-146393
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Outcomes for Pediatric and Young Adult Patients with Relapsed or Refractory (R/R) B-Cell Acute Lymphoblastic Leukemia (ALL) Treated with Tisagenlecleucel: Update from the Center for International Blood and Marrow Transplant Research (CIBMTR) Registry

Abstract: Background: Tisagenlecleucel is an autologous CD19-directed T-cell immunotherapy indicated in the USA for treatment of patients up to 25 years (y) of age with B-cell ALL that is refractory or in second or later relapse. Overall response rate was 82% with 24 months' (mo) follow-up in the registrational ELIANA trial [Grupp et al. Blood 2018]; pooled data from ELIANA and ENSIGN revealed similar outcomes upon stratification by age (<18y and ≥18y) [Rives et al. HemaSphere 2018]. Early real-world data for tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…For patients who first visited the ED later (>14 days of CAR T product infusion), in whom we observed worse overall survival outcomes, it is known that cancer patients frequently visit the ED near the end of life, with reasons mainly related to cancer progression (22). Moreover, and as previously reported, post CAR T relapse can be observed early after infusion and is associated with poor overall survival, mainly due to the persistence or progression of the primary malignant disease (23,24).…”
Section: Discussionmentioning
confidence: 90%
“…For patients who first visited the ED later (>14 days of CAR T product infusion), in whom we observed worse overall survival outcomes, it is known that cancer patients frequently visit the ED near the end of life, with reasons mainly related to cancer progression (22). Moreover, and as previously reported, post CAR T relapse can be observed early after infusion and is associated with poor overall survival, mainly due to the persistence or progression of the primary malignant disease (23,24).…”
Section: Discussionmentioning
confidence: 90%
“…According to the CIBMTR study, real-world tisa-cel treatment in children and young adults with R/R B-ALL seems to be effective across all age groups and similar to findings reported from the ELIANA trial. 54,55 At a median follow-up of 25.9 months, the ORR was 86.8% (vs 82.3% in ELIANA) and MRD-negative response was achieved by 97.9% of patients (vs 98.5%), with DoR of 61.4% (vs 67.4%). Also, the EFS rate at 12 months in the CIBMTR registry was comparable with that observed in ELIANA (52.6% vs 57.2%).…”
Section: New Data On Car T-cell Therapies For B-cell Acute Lymphoblas...mentioning
confidence: 98%
“…At the 2021 American Society of Hematology (ASH) annual meeting, real-world outcomes of tisa-cel treatment of pediatric and young adult patients with R/R B-ALL showed that, after a median follow-up of 21.5 months (11.9-37.2 months), the median eventfree survival (EFS) was 14.0 months (95% confidence interval (CI), 9.8-24.8) and the median relapse-free survival (RFS) was 23.9 months (13.0-not estimated (NE)). The 12-month EFS rate was 54.3% and the RFS rate was 62.3% (John et al, 2021). In axi-cel-treated patients with R/R large B-cell lymphoma (LBCL), a 12-month EFS rate of 43% (95% CI, 33%-52%) and a 24-month EFS rate of 38% (95% CI, 28%-47%) were reported (Jacobson et al, 2021).…”
Section: Clinical Relevancementioning
confidence: 99%